SYNTHESIS OF AIR TRAFFIC CONTROLLING ON THE BASE OF ARTIFICIAL GRAVITATIONAL FIELDS METHOD USING - Chepizhenko, Valeriy; Solomina, Nataliia (Proceedings of National Aviation University (archive), 2014)
For investigation of artificial gravitational fields method was modeled the movement of two conflicting aircraft with the different angles of Ψ, was presented the area of the control states with the degrees of development.